Primary Teachers’ Mathematics Anxiety and Mathematics Teaching Anxiety as Predictors of Students’ Performance in Mathematics - Adeneye Olarewaju A. Awofala; Sabainah O. Akinoso; Comfort O. Adeniyi; Sufiyanu H. Jega; Alfred O. Fatade; Abayomi A. Arigbabu (ASEAN Journal of Science and Engineering Education, 2024)
The study investigated primary teachers’ mathematics anxiety as related to mathematics teaching anxiety and students’ performance in mathematics among 480 primary teachers from twenty public primary schools. The study adopted the quantitative research method within the blueprint of the descriptive survey design. Findings revealed that test anxiety, course anxiety, application anxiety, computation anxiety, social anxiety, content knowledge teaching anxiety, self-confidence teaching anxiety, attitudes toward mathematics teaching anxiety, and teaching knowledge anxiety jointly contributed to a coefficient of multiple regression of 0.501 and a multiple correlation square of 0.251 to the prediction of student's performance in mathematics. By implication, 25.1% of the total variance of the dependent variable (performance in mathematics) was accounted for by the combination of the nine independent variables. Based on this study, it was thus, recommended that future studies in Nigeria and elsewhere should investigate the factor analytic structure of the mathematics teaching anxiety scale among in-service and preservice teachers of mathematics.